2014
DOI: 10.1007/s10456-014-9420-y
|View full text |Cite|
|
Sign up to set email alerts
|

Anti-angiogenic therapy for cancer: current progress, unresolved questions and future directions

Abstract: Tumours require a vascular supply to grow and can achieve this via the expression of pro-angiogenic growth factors, including members of the vascular endothelial growth factor (VEGF) family of ligands. Since one or more of the VEGF ligand family is overexpressed in most solid cancers, there was great optimism that inhibition of the VEGF pathway would represent an effective anti-angiogenic therapy for most tumour types. Encouragingly, VEGF pathway targeted drugs such as bevacizumab, sunitinib and aflibercept ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
588
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 628 publications
(603 citation statements)
references
References 247 publications
8
588
0
7
Order By: Relevance
“…Las células tumorales producen sustancias activadoras de la angiogénesis o pro angiogéni-cas, pues la neovascularización es imprescindible para el desarrollo de tumores mayores de 2 o 3 mm. El VEGF está sobreexpresado en la mayoría de los cánceres sólidos, por lo que la inhibición de esta vía de señalización (signalling pathway) pro angiogéni-ca se ha convertido en un objetivo preciso para suprimir el crecimiento tumoral (14) . El VEGF no solamente estimula la angiogénesis sino que es un factor de sobrevivencia del endotelio vascular y promueve un fenotipo de vasos sanguíneos anormales dentro de los tumores (15) .…”
Section: Drogas Inhibidoras De La Angiogénesis (Ia) E Hipertensión Arunclassified
See 3 more Smart Citations
“…Las células tumorales producen sustancias activadoras de la angiogénesis o pro angiogéni-cas, pues la neovascularización es imprescindible para el desarrollo de tumores mayores de 2 o 3 mm. El VEGF está sobreexpresado en la mayoría de los cánceres sólidos, por lo que la inhibición de esta vía de señalización (signalling pathway) pro angiogéni-ca se ha convertido en un objetivo preciso para suprimir el crecimiento tumoral (14) . El VEGF no solamente estimula la angiogénesis sino que es un factor de sobrevivencia del endotelio vascular y promueve un fenotipo de vasos sanguíneos anormales dentro de los tumores (15) .…”
Section: Drogas Inhibidoras De La Angiogénesis (Ia) E Hipertensión Arunclassified
“…El lugar principal de los agentes IA se encuentra en la etapa metastásica del cáncer, pero la respuesta no es igual en todos los tipos de tumores (14) .…”
Section: Modalidades De Uso De Las Drogas Inhibidoras De La Angiogénesisunclassified
See 2 more Smart Citations
“…Bev is a recombinant, humanized, monoclonal antibody against the VEGF approved by the Food and Drug Administration for the first-line treatment of non-SCLC and other solid tumors. [11][12][13] Because results in preclinical models suggested that angiogenesis is an important factor for tumor growth, Bev might also play a role in the treatment of SCLC. 14 A few clinical studies on platinum-based chemotherapy with Bev followed by Bev as maintenance treatment have led to promising survival results in ED-SCLC.…”
Section: Introductionmentioning
confidence: 99%